Crude Drugs Standardization, Total Flavonoid and Phenolic Content Profile, and Antimicrobial Activity of Red Ginger and Lemongrass Combination - Puspitasari, Adinda; Hamad, Alwani; Hartanti, Dwi (Jurnal Tumbuhan Obat Indonesia, 2024)
Baturraden people use a combination of red ginger rhizomes and lemongrass leaves for the treatment of masuk angin. This study aims to evaluate the quality profile of red ginger and lemongrass crude drug, total flavonoid content (TPC), total phenolic content (TFC), and the antimicrobial activities of their combination water extracts. The quality of both crude drugs was standardized to Indonesian Herbal Pharmacopeia (IHP). The TPC and TFC of red ginger and lemongrass combination in five different ratios were determined by standard UV-Vis spectrophotometry methods. The antimicrobial activity was evaluated using the microdilution method against patient-isolated multidrug-resistant (MDR) Staphylococcus aureus and Candida albicans. Lemongrass crude drugs were of good quality, while red ginger did not meet the acid-insoluble ash and volatile matter content requirements. The combination showed the highest TFC in a 75:25% ratio, while that of TPC was 50:50%. All combinations of lemongrass and red ginger extracts inhibited MDR Staphylococcus aureus and Candida albicans with a minimum inhibitory concentration (MIC) of 0.16 mg/ml. Candida albicans were more susceptible to the combination extracts. Red ginger rhizomes and lemongrass leaves 75:25% and 50:50% ratios showing comparable effects to the respective components. Hence, the combination of red ginger and lemongrass in 75:25 and 50:50% ratios potentially developed further for their masuk angin efficacy.